Analysis of the importance of non swum parts in a 800m freestyle test according to gender and level of expertise - Delaplace-Reisser, C.; Chollet, D. (First international symposium sciences and practices in swimming, 2006)
The non swum parts like turning, but also starting or the arrival have an outstanding influence on the performance. This importance is conversely proportional to the stroke distance. On 800m, it appears that more than one third of the race time is devoted to turning (34,7%) and 1% is devoted to starting and the arrival. The results of this study show that the non expert swimmers, instead of being helped by the non swum parts allowing them to push from the wall, are penalized by the number of turns. Their lack of technique, mainly respiratory , causes a break in the keeping of the hydrodynamic balance. Finally the males exert more strength at the time of the departure and during the turns, and are proportionally faster than the females in the turns.